Confocal laser scanning microscopic analysis of ectopic sublingual gland‐like tissue inside the hamster submandibular gland. Issue 12 (9th October 2013) - Moriguchi, Keiichi; Utsumi, Michiya; Ohno, Norikazu
ABSTRACT Based on its histochemical properties, the secretory portion of the hamster submandibular gland has been classified as seromucous cells. The presence of endogenous peroxidase (PO) reaction was shown in the nuclear envelope, cisternae of endoplasmic reticulum and Golgi apparatus. The 3, 3′‐diaminobenzidene, tetrahydrochloride (DAB) method revealed bipartite secretory granules containing a PO‐positive dense core surrounded by a less dense halo in these cells. In the present investigation, serous and mucous‐like cells were found in resin‐embedded semi‐thin sections of the DAB‐reacted hamster submandibular gland. These sections were already on glass slides for routine light microscopic observations, therefore electron microscopic analysis could be unrealizable. We then used reflectance‐mode confocal laser scanning microscopy to visualize additional sites of PO activity as detected in these sections. Using this approach, we found mucous cells with PO activity‐negative secretory granules and seromucous cells with PO activity‐positive spot‐like secretory granules of the regular sublingual gland most frequently adjacent to the serous cells with typical electron‐dense secretory granules. These cells clearly differ from the seromucous cells with bipartite secretory granules and the granular duct cells with typical electron‐dense secretory granules of the hamster submandibular gland. Additionally, secretory endpieces of the ectopic sublingual gland‐like tissue empty into the duct of the hamster submandibular gland lobule. Thus, our findings suggest that a mass of sublingual gland tissue extends into the hamster submandibular gland during its development, and PO may be synthesized and secreted into the same duct. Microsc. Res. Tech. 76:1284–1291, 2013. © 2013 Wiley Periodicals, Inc.